Increasing Students’ Motivation and Ability to Write Descriptive Text Using Social Media and Photo Comics in PBL Method - Hetty Dwi Agustin (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2023)
Students always have difficulty in writing composition using English. This encourages teachers to conduct research. The purpose of study is to improve students' motivation and ability in writing descriptive text, using social media and photo comics. The social media used in this research are Youtube and Whatsapp which support the learning process. Meanwhile, the photo comic used in this study is expected to be of interest to students, so that it can encourage students to be motivated in learning English, including being eager to write Descriptive Text. Because students interested in photo comics and make them easy to write. Students are helped to make some sentences by images of photo comic. The method used in this research is Project Based Learning (PBL). The subjects are 7th grade students of SMPN 8 Surakarta in second semester 2021/2022. Students had to achieve the Base Competence of English Curriculum 7th grade 4.7.2 that is Compiling oral and written descriptive texts, very short and simple, related to people, animals, and objects that they like by paying attention to social functions, text structure, and linguistic elements, correctly and in context. The results showed that social media and photo comics are very effective in increasing students' motivation and ability to write descriptive text. They are very interesting and effective sources of ideas for students in writing the text. Finally, students increased their motivation and ability in writing Descriptive Text, and also can reach the Base Competence of English curriculum of 7th grade (KD 4.7.2.).